If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4+9q=10q+3
We move all terms to the left:
-4+9q-(10q+3)=0
We get rid of parentheses
9q-10q-3-4=0
We add all the numbers together, and all the variables
-1q-7=0
We move all terms containing q to the left, all other terms to the right
-q=7
q=7/-1
q=-7
| x-3.2=5.43 | | 0.6p=-4.8 | | 8x-5-4x=37-2x | | 4a-4+5a=14 | | x+1/2=x+5/4 | | 8r=9r-10 | | 10)6(2r+5)=126 | | 5+7s=232 | | 94=m/10–84 | | 5h=4+9h | | 8x²-7=10x | | y+3.7=4.8 | | 4-9n=1-10n | | |6r-4|=38 | | 2=v/4-4 | | h/7-35=-29 | | 6(-2-2x)=84 | | -y/9=-21 | | -2(-9-7x)=-80 | | 45=15+z | | (X+20)+3x+32=180 | | 5n+2+6n=-9 | | 3(z-96)=45 | | 15=k4+ 11 | | 60=-u/4 | | 4+6b=46 | | 5(1x-5)=-40 | | d/6+26=29 | | x+2.4=86 | | 10=-8x+58 | | 20/x6/15= | | 6/24=x/288x= |